The Ability to Understand Spatial Concepts of Disaster Mitigation Materials Through Problem Based Learning Model - Eka Anjar Sari; Erni Suharini; Eva Banowati (International Conference on Science, Education, and Technology, 2021)
The ability of understanding the concept of spatial disaster mitigation is important for students in their daily lives. The problem is that the learning process in the classroom is still less than optimal, which has an impact on the low ability of students to understand spatial concepts. The aim of this study is to analyze the ability of understanding the concept of spatial students through the Problem Based Learning model on disaster mitigation materials in SMA Pondok Modern Selamat Kendal. This research method used is an experiment method using pretest-posttest control and experimental design. The sampling technique is random sampling from XI IPS class. Data collection techniques through test, observation, and questionnaires. The measurement of increasing the ability is obtained from the normalization gain calculation. The results showed an increase in the ability to understand spatial concepts in the experimental class with an average gain score of 62.74% belonging to the medium category and the control class with an average gain score of 20.70% belonging to the low category. In the independent t-test obtained significance value (sig < 0.05) sig 0.00 which means accepted or there is a significant influence between the learning model of Problem Based Learning on increasing the ability of understanding the concept of spatial disaster mitigation materials. The response of students to positive learning and included in the very good category.